2008
DOI: 10.1253/circj.72.370
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Dyssynchrony During Development of Heart Failure by a Novel Program Using ECG-Gated Myocardial Perfusion SPECT

Abstract: Background A novel program, "cardioGRAF", has been developed to analyze regional left ventricular (LV) systolic/diastolic function and dyssynchrony, so the present study aimed to use it confirm the presence of LV dyssynchrony, and to correlate LV function and dyssynchrony with plasma B-type natriuretic peptide (BNP) levels during the early to advanced stages of heart failure (HF). Methods and ResultsFourteen control subjects (G-C) and 50 patients (New York Heart Association functional class I: G-1, 21 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Recent studies suggest that LV dyssynchrony is also common in patients with narrow QRS and heart failure with preserved EF 19 , as well as those with hypertension with LV hypertrophy 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that LV dyssynchrony is also common in patients with narrow QRS and heart failure with preserved EF 19 , as well as those with hypertension with LV hypertrophy 20 .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Furthermore, recent studies showed that the BNP level predicted subsequent prognosis not only in patients with heart failure but also in those with CAD. 1,3,4 In the present posthoc analysis of the Q-PROVE study, a high BNP level >130 pg/ml was significantly associated with subsequent cardiac events in 102 elderly patients with known or suspected CAD.…”
Section: Discussionmentioning
confidence: 99%
“…10 The LV is divided into (Received April 27, 2008; revised manuscript received August 5, 2008; accepted August 19, 2008; released online January 9, 2009) Departments of Cardiology, *Cardiovascular Surgery, Edogawa Hospital and **Medtronic Japan Co Ltd, Tokyo, Japan Mailing address: Takehiko Keida, MD, Department of Cardiology, Edogawa Hospital, 2-24-18 Higashi Koiwa, Edogawa-ku, Tokyo 133-0052, Japan. E-mail: keida@edogawa.or.jp All rights are reserved to the Japanese Circulation Society.…”
Section: Case Report Data Acquisition and Analysis With Cardiografmentioning
confidence: 99%
“…10 The LV is divided into 17 volume segments, 11 and the regional wall motion and change in myocardial wall thickening of each segment are estimated. [12][13][14] The variation in volume over time is measured for each segment, where the onset of a cardiac rhythm is triggered on the peak of the R-wave, and the instant of end-systole is detected using the zero-crossing detection on the first-derivative of the time-volume curve (ie, contraction velocity.…”
Section: Case Report Data Acquisition and Analysis With Cardiografmentioning
confidence: 99%